Characterizing sexual function in patients with generalized anxiety disorder: a pooled analysis of three vilazodone studies - Clayton A; Durgam S; Tang X; Chen C; Ruth A; Gommoll C (Neuropsychiatric Disease and Treatment, 2016)
Anita H Clayton,1 Suresh Durgam,2 Xiongwen Tang,2 Changzheng Chen,2 Adam Ruth,3 Carl Gommoll2 1Department of Psychiatry and Neurobehavioral Sciences, University of Virginia, Charlottesville, VA, 2Forest Research Institute, Jersey City, NJ, 3Prescott Medical Communications Group, Chicago, IL, USA Background: Vilazodone has been shown to reduce core symptoms of generalized anxiety disorder (GAD) in three randomized, double-blind, placebo-controlled trials. Since sexual dysfunction (SD) is not well characterized in GAD, a post hoc analysis of these trials was conducted to evaluate the effects of vilazodone on sexual functioning in GAD patients. Materials and methods: Data were pooled from one fixed-dose trial of vilazodone 20 and 40 mg/day (NCT01629966) and two flexible-dose studies of vilazodone 20–40 mg/day (NCT01766401, NCT01844115) in adults with GAD. Sexual functioning was assessed using the Changes in Sexual Functioning Questionnaire (CSFQ). Outcomes included mean change from baseline to end of treatment (EOT) in CSFQ total score and percentage of patients shifting from SD at baseline (CSFQ total score ≤47 for males, ≤41 for females) to normal functioning at EOT. Treatment-emergent adverse events related to sexual functioning were also analyzed. Results: A total of 1,373 patients were included in the analyses. SD at baseline was more common in females (placebo, 46.4%; vilazodone, 49%) than in males (placebo, 35.1%; vilazodone, 40.9%). CSFQ total score improvement was found in both females (placebo, +1.2; vilazodone, +1.6) and males (placebo, +2.1; vilazodone, +1.0), with no statistically significant differences between treatment groups. The percentage of patients who shifted from SD at baseline to normal sexual functioning at EOT was higher in males (placebo, 40.6%; vilazodone, 35.7%) than in females (placebo, 24.9%; vilazodone, 34.9%); no statistical testing was performed. Except for erectile dysfunction and delayed ejaculation in vilazodone-treated males (2.4% and 2.1%, respectively), no treatment-emergent adverse events related to sexual functioning occurred in ≥2% of patients in either treatment group. Conclusion: Approximately 35%–50% of patients in the vilazodone GAD studies had SD at baseline. Vilazodone and placebo had similar effects on CSFQ outcomes in both females and males, indicating a limited adverse impact on sexual functioning with vilazodone. Keywords: vilazodone, generalized anxiety disorder, sexual dysfunction, clinical trials, post hoc analysis